The Pattern Of Islamic Education Of The Pepe Village Comunity As A Manifestation Of A Culturally Accommodating Islamic Society - Nadava Aulia; Budi Haryanto (At-Tarbiyat, 2023)
This research examines the pattern of Islamic education in the Pepe village community. Indonesia is a country that has a pluralistic society, including religion, race, ethnicity and culture. This pluralism often has the potential for the emergence of various conflicts as society becomes increasingly dynamic in grouping itself into various religious social organizations and the birth of various religious sects. Excessive fanaticism often fosters a spirit of sectoral ego which can threaten the disintegration of the nation. The emergence of various conflict phenomena in Indonesia in the name of religion is an indicator that the Indonesian nation still does not fully understand the internal conditions of its own nation which has a multicultural background. Differences in a multicultural society should be the basis for maintaining each individual's identity while maintaining national integration, not to trigger the birth of conflicts between groups which, if examined more deeply, the actual motives are not entirely due to religious factors, but social factors. cultural, political and even economic motives. Through multicultural Islamic education, this article provides an alternative resolution of religious conflicts in Indonesia based on the values ​​contained in Islamic teachings regarding the importance of respecting the diversity of every multicultural societal structure. Multicultural Islamic education can be used as a new approach that can change people's way of thinking and perspective as well as attitudes and behavior skills in a pluralistic life. In this context, multicultural Islamic education provides the cultivation of a spirit of religious life that is based on the values ​​of peace, tolerance, respect for differences and other attitudes that uphold human values ​​and the spirit of Indonesian national unity